2018
DOI: 10.1177/1528083718763779
|View full text |Cite
|
Sign up to set email alerts
|

Hydroentangled nonwoven eri silk fibroin scaffold for tissue engineering applications

Abstract: Electrospun scaffolds are being widely studied for its potential application in tissue engineering because of its nanostructure that mimics the extracellular matrices. Although it has several advantages, it lacks mechanical strength and causes structural deformation during handling of the scaffold. It is well known that the textile-based structures like woven and nonwoven fabrics have excellent structural stability. In this study, a woven and a hydroentangled nonwoven fabric were fabricated from eri silk fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Furthermore, the exceptional biocompatibility of SF with a diversity of cells and tissues, and also, its efficient potential in promoting cellular adhesion and proliferation of fibroblasts and keratinocytes have been approved 27 29 . This natural protein can be formed in different material shape and structures such as hydrogel 30 , film 31 , nonwoven fabrics 32 , nanofiber 33 , and 3D porous scaffolds 34 . However, alongside its super mechanical property, studies have been indicated that its combination with other materials such as graphene oxide 35 , natural polymers 28 , 36 , metal nanoparticles 37 , 38 , and the formation of SF-based composite can enhance the antimicrobial property of SF; which is essential factor for wound dressing use.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the exceptional biocompatibility of SF with a diversity of cells and tissues, and also, its efficient potential in promoting cellular adhesion and proliferation of fibroblasts and keratinocytes have been approved 27 29 . This natural protein can be formed in different material shape and structures such as hydrogel 30 , film 31 , nonwoven fabrics 32 , nanofiber 33 , and 3D porous scaffolds 34 . However, alongside its super mechanical property, studies have been indicated that its combination with other materials such as graphene oxide 35 , natural polymers 28 , 36 , metal nanoparticles 37 , 38 , and the formation of SF-based composite can enhance the antimicrobial property of SF; which is essential factor for wound dressing use.…”
Section: Introductionmentioning
confidence: 99%
“…The existing facial mask paper mainly made of cellulosic fibers or chemical fibers as raw materials into nonwoven webs in one or more nonwoven web forming methods, are reinforced by spunlace [1][2][3][4][5] and others, which is a long production process as shown in Figure 1. The facial mask paper made of these fibers are poor in skin affinity, which just function as essence carrier without bionic intelligence.…”
Section: Introductionmentioning
confidence: 99%
“…2,5 There is no obvious boundary between the cocoon layer and the cocoon coat, and the inner layer of the silkworm cocoon is tight. 6,7 Due to its own structure, the eri silkworm cocoon is not suitable for continuous reeling, but is only used for silk spinning or used as filling material in a few areas, 8 the economic benefits are lower.…”
Section: Introductionmentioning
confidence: 99%